(τ1, τ2)α-Continuity for Multifunctions - Chokchai Viriyapong; Chawalit Boonpok (Journal of Mathematics)
The main goal of this article is to introduce the concepts of upper and lower (τ1, τ2)α-continuous multifunctions. Characterizations of upper and lower (τ1, τ2)α-continuous multifunctions are investigated. The relationships between upper and lower (τ1, τ2)α-continuous multifunctions and the other types of continuity are discussed.